Postheparin plasma diamine oxidase increases in patients with coeliac disease during gluten free diet. (1987) - D'Agostino, L; Daniele, B; Pignata, S; Barone, M V; Ciacci, C; Sollazzo, R; Mazzacca, G
Abstract : An intravenous injection of heparin releases diamine oxidase (DAO) from villous tip enterocytes. In a previous study, we found that postheparin plasma DAO (PHD) values were significantly lower in patients with malabsorption syndrome and small bowel atrophy at jejunal biopsy than in normal subjects. In this study we performed the PHD test in 14 coeliac patients before and after three and six months of gluten free diet to show whether the enterocytes maturing processes induced by the diet joined with enhanced PHD values and to assess the clinical usefulness of this test. In all subjects jejunal biopsy carried out after six months showed a partial but consistent histological recovery. The clinical status, xylosuria and daily faecal fat excretion improved progressively and there was a significant increase (p less than 0.001) in mean PHD activity that reached the normal range after three months. After six months a further slight increase of the mean PHD value was recorded. These data indicate that PHD values rise together with the improved intestinal absorptive functions of coeliac patients on gluten free diet and that this test is a useful tool in monitoring recovery of the small bowel mucosa.